Improve the signal to noise ratio using AND subtraction technique in optical CDMA - Mohamad, Othman; Noran Azizan, Cholan; Rahmat M., Talib; Baharadin, E.; Rejab, M. F M; Syed Alwee Aljunid, Syed Junid; Mohamad Khazani, Abdullah (ACTA Press, 2010)
Link to publisher's homepage at http://www.actapress.com